PEOPLE'S PERCEPTION OF THE MYTH OF "KEPUNAN" IN BANGKA BELITUNG ISLANDS PROVINCE: PERSEPSI MASYARAKAT TERHADAP MITOS “KEPUNAN” DI PROVINSI KEPULAUAN BANGKA BELITUNG - Dwianita Conny Palar; Derinta Entas; Siti Husnul Khotimah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This study aims to determine the people's perception of the myth of "kepunan" in the Bangka Belitung Islands Province. This research method uses descriptive qualitative with triangulation techniques, namely observation, interviews, and documentation. The sampling technique uses Purposive sampling. The object of research in the Bangka Belitung Islands Province, where the myth is still developing and believed in, is the myth of "kepunan.” This myth is viewed from three aspects: cultural views, religion, and the younger generation. These three aspects became the basis for obtaining the results of this study. First, the myth of " kepunan " is part of the culture and customs of local peoples passed down from generation to generation from ancestors. Most local people believe in the myth of "kepunan" and think that there is something terrible that comes if they ignore the myth. Other minority groups believe the myth of "kepunan" is an ancestral heritage that needs to be maintained as local wisdom in Bangka Belitung. Second, the group of scholars believes that the myth of " kepunan " is only a mere superstition, unacceptable with logic, and cannot be accounted for its truth, so the myth cannot be connected with religious rules. Third, the younger generation's view of this "kepunan" myth has begun to diminish because environmental factors influence it. Where the younger generation of the local people of Bangka Belitung worked a lot in the city, so slowly, the myth of "kepunan" began to fade.